2020
DOI: 10.1101/2020.09.21.305854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale characterization of sex pheromone communication systems inDrosophila

Abstract: Insects use sex pheromones as a reproductive isolating mechanism to attract conspecifics and repel heterospecifics. Despite the profound knowledge of sex pheromones, little is known about the coevolutionary mechanisms and constraints on their production and detection. Using whole-genome sequences to infer the kinship among 99 drosophilids, we investigate how phylogenetic and chemical traits have interacted at a wide evolutionary timescale. Through a series of chemical syntheses and electrophysiological recordi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 87 publications
(94 reference statements)
2
11
0
Order By: Relevance
“…Within the 10 minutes, however, all of the flies had copulated except DGRP882 males paired with Z53 males. We did not find however, known "female" CHCs on the males, confirming that any changes to the males were not the result of female CHCs rubbing off of males (KHALLAF et al 2020b). Quantification of CHCs is described in the Supplemental Information.…”
Section: Cuticular Hydrocarbon Collection and Quantificationsupporting
confidence: 64%
See 1 more Smart Citation
“…Within the 10 minutes, however, all of the flies had copulated except DGRP882 males paired with Z53 males. We did not find however, known "female" CHCs on the males, confirming that any changes to the males were not the result of female CHCs rubbing off of males (KHALLAF et al 2020b). Quantification of CHCs is described in the Supplemental Information.…”
Section: Cuticular Hydrocarbon Collection and Quantificationsupporting
confidence: 64%
“…Female-genotype-dependent courtship plasticity suggests that males require lineage-specific female cues for successful courtship (BARKER 1967;COBB AND JALLON 1990;SEEHOLZER et al 2018). CHCs can both stimulate and inhibit mating (FERVEUR 2005;GRILLET et al 2006;EJIMA et al 2007;KHALLAF et al 2020a;KHALLAF et al 2020b), and a strong difference exists in the female CHCs of Z-type and M-type females (COYNE et al 1999;DALLERAC et al 2000). The ability of males to change their courtship can alter their courtship in subsequent mating interactions, which are typically not considered in the study of speciation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the atrophied ejaculation bulb of the D. suzukii male does not produce cVA (Dekker et al, 2015). Some Drosophila species do not produce but still detect cVA (Khallaf et al 2020). Electrophysiological recording revealed that the D. melanogaster and D. suzukii females both can able to detect cVA by olfactory neurons in antennal trichoid sensilla (Khallaf et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Some Drosophila species do not produce but still detect cVA (Khallaf et al 2020). Electrophysiological recording revealed that the D. melanogaster and D. suzukii females both can able to detect cVA by olfactory neurons in antennal trichoid sensilla (Khallaf et al, 2020). cVA bind to the DmOBP69a (Bentzur et al, 2018) and DmOBP76a (Billeter and Levine, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation